Wide temperature range protection performance of Zr–Ta–B–Si–C ceramic coating under cyclic oxidation and ablation environments - Guo Xiaoyang; Tian Yuan; Wang Na; Jiang Yan (High Temperature Materials and Processes, 2025)
In order to improve the oxidation and ablation resistance of carbon materials, Zr–Ta–Si–C–B coatings with different Zr/Ta ratios were successfully prepared on the graphite surface by combining slurry impregnation and reactive melt infiltration (RMI). The coatings after RMI are dense, Zr–Ta–B solid solution, SiC, and Si coexist in the coating where ceramic particles are tightly wrapped by Si. The cycle oxidation test results at 1,600°C for 100 h (5 h × 20 cycles) show that the Zr–Ta–Si–C–B coating with a Zr/Ta ratio of 4:6 has a better anti-oxidation effect; the mass change rate of the coated specimen is −0.26%. Its good oxidation protection performance is mainly due to the generated Zr and Ta oxides on the coating surface, which increase the viscosity of the SiO2 layer and effectively block the diffusion channels of oxygen. After ablation at 2,300°C for 480 s, the mass ablation rate and linear ablation rate of the Z4T6 coating are 1.48 × 10−2 mg·s−1 and 0.94 μm·s−1, respectively. The Zr–Ta–Si–O composite glass layer composed of (Zr,Ta)O2 and SiO2 is relatively intact at the early stage of ablation, and it can effectively prevent plasma flame ablation. After four cycles of ablation (120 s × 4 cycles), the (Zr,Ta)O2 solid solution and SiO2 generated by the ablation reaction are insufficient to resist the invasion of high-temperature oxygen and flame erosion, ultimately leading to the failure of coating protection.